Energy Efficiency Analysis through Misalignment on New Design of Hexagonal Coil Array in Wireless Power Transfer - Hidayat, Taufik; Tigor Franky D , Sianturi; Mahardiko, Rahutomo (International Journal of Integrated Engineering, 2020)
The global transportation revolution accelerates the growth of the Electric Vehicle (EV) market. Wireless Power Transfer Technology (WPT) is part of an alternative solution to replace charging by cable. In its implementation the driver’s parking behavior affects Power Transfer Efficiency (PTE) due to frequently misalignment. A new coil array design proposed to optimize PTE and reduce the size of receiver coil. Receiver and transmitter circuits designed to simulate parking conditions and parking lots in small scale settings to get PTE data. Experimental results show that PTE increased by 10% in the center of the coil design and 82% during misalignment on a radius array against single loop coil. In the area of Misalignment tangential boundary, efficiency increased by 5-10% compared to circular coil arrays. The proposed novel coil series achieves a higher overall PTE than a single coil design and an increase in PTE in the tangential boundary misalignment when compared to circular coil arrays.